Urban environmental noise and depression causal pathway: Potential role of chronic conditions as mediator - Enrique Sanz Olea; Jesus León Hernández; Begoña Artíñano; Verónica Briz; Spyros Karakitsios; Dimosthenis Sarigiannis; Saul García Dos Santos; Beatriz Nuñez-Corcuera; Rebeca Ramis (PLoS ONE, 2025)
Background Accepting the fact of a growing urban population and associated health risks, such as increased exposure to pollutants, and considering the high prevalence of chronic diseases, this study aims to investigate the relationship between exposure to environmental noise and depression. The primary objective is to determine the potential mediating role of chronic diseases in this relationship. This study is part of the European H2020 URBANOME project, designed to explore the relationship between the environment and health in urban settings. The main goal of the project is to promote urban health, well-being, and liveability by systematically integrating health concerns into urban policies and civic activities. Materials and methods We obtained the data for this study from the Madrid City Health Survey, conducted through computer-assisted telephone interviews. Outcome variables assessed through self-reports included depression, exposure to environmental noise, and the presence of chronic diseases. We used a counterfactual mediation framework, implemented by the R package multimediate, to evaluate the potential mediating role of chronic diseases in the relationship between exposure to environmental noise and depression. Results The study included 8,445 interviews, with a higher percentage of women (54.67%) than men. 23.29% were over 65, and 17.17% under 30. Notably, 7.82% reported depression, 39.53% had chronic diseases, and 35.43% acknowledged noise exposure. In our regression models, those exposed to environmental noise were 1.24 times more likely to have a chronic disease, and individuals with a chronic disease were 2.93 times more likely to suffer from depression. Participants exposed to environmental noise had 1.03 times more depression, being the 13% of the noise health effect mediated by the presence of chronic illness. Conclusion Our findings suggest a link between environmental noise exposure and depression, potentially mediated by chronic diseases. This points out the need for public health interventions to reduce urban noise exposure and improve mental health. Furthermore, prospective studies are needed for confirmation, incorporating noise level measurements and temporal data on the onset of chronic diseases and depression.